The Influence Of Accountability, Transparency, And Information Technology On The Quality Of Public Services (Case Study At Bpjs Ketenagkerjaan Purwakarta) - Rahmat Salamet, R.Apit; Putri Ariyanto, Dea; Jatnika, Ika (Journal of Management, 2025)
This study aims to determine the effect of accountability, transparency, and information technology on the quality of public services partially and simultaneously. The method used in this study is a quantitative method, the data sources used are primary data and secondary data. To obtain data in this study is distributed questionnaires through Google Forms online and barcode offline. The population in this study were all participants of BPJS Ketenagakerjaan Purwakarta. The number of samples in this study was 100 respondents using the Slovin formula. The sampling technique used was purposive sampling with the criteria of participants registered with BPJS Ketenagakerjaan Purwakarta. Testing of the research variables was conducted using the Structural Equation Modeling (SEM) method with the SmartPLS 4 application. The results of the study indicate that Accountability, Transparency, and Information Technology have a significant positive effect on the Quality of Public Services. Accountability with a P-Value of 0.012 <0.05, a T-statistic value of 2.527> 1.98 and a positive original sample of 0.275. Furthermore, Transparency with a P-Value of 0.003 <0.05 and a T-statistic value of 2.973 > 1.98 with a positive original sample of 0.383. And Information Technology with a P-Value of 0.023 <0.05 and a T-statistic value of 2.268 > 1.98 with a positive original sample of 0.296. Furthermore, the results of the coefficient of determination (R-Square) are 0.736 or 73.6% included in the strong category, which means that the variable of Public Service Quality can be explained strongly by Accountability, Transparency, and Information Technology.